Assessment of the Crop Forcing Technique and Irrigation Strategy on the Ripening of Tempranillo Grapes in a Semiarid Climate - Nieves Lavado; David Uriarte; Luis A. Mancha; Daniel Moreno; M. Esperanza Valdés; M. Henar Prieto (Australian Journal of Grape and Wine Research)
To the memory of Jordi Marsal